A new earth awakening to your life's purpose - Tolle, Eckhart 1948- (New York, N.Y Dutton/Penguin Group, 2005)
Tolle presents readers with an honest look at the current state of humanity: he implores us to see and accept that this state, which is based on an erroneous identification with the egoic mind, is one of dangerous insanity. However, there is an alternative to this potentially dire situation. Humanity now, perhaps more than in any previous time, has an opportunity to create a new, saner, more loving world. This will involve a radical inner leap from the current egoic consciousness to an entirely new one. In illuminating the nature of this shift, Tolle describes in detail how our current ego-based state of consciousness operates. Then gently, and in very practical terms, he leads us into this new consciousness. We will come to experience who we truly are--which is something infinitely greater than anything we currently think we are.--From publisher description
The flowering of human consciousness -- Ego : the current state of humanity -- The core of ego -- Role-playing : the many faces of the ego -- The pain-body -- Breaking free -- Finding who you truly are -- The discovery of inner space -- Your inner purpose -- A new earth
Includes bibliographical references (p. 311-313)
1
Keywords: Spiritual life